Analysis of Utsmani Method in Improving Memorization of the Quran at the Islamic Boarding School of Asaefurrohimi Sulaimaniyah Jasinga Bogor - Bilqis, Mariatul; Irfani, Fahmi; Kamaluddin, Kamaluddin (Lembaga Yasin AlSys, 2025)
This study aims to analyze the implementation process of the Ustmani Method in enhancing students' memorization at the Islamic Boarding School of Sulaimaniyah Asaefurrohim Jasinga Bogor. It identifies factors influencing both the success and challenges of memorization and evaluates the method's impact on students' memorization and comprehension. The researchers employed a descriptive qualitative approach utilizing field research methods, with data collected through in-depth interviews, observations, and documentation. The results indicate that the Ustmani Method is effective in improving students' memorization through a systematic loop repetition system. Students do not memorize sequentially; rather, they follow a specific pattern that enhances memory, specifically through a backward sequence system. Key success factors for this method include consistency, discipline in murojaah, and support from teachers and the surrounding environment. However, challenges such as inconsistent student participation, time constraints, and variations in individual memory capabilities remain obstacles to its implementation. Periodic evaluations are conducted through tiered memorization assessments and examinations at designated intervals, which assist students in maintaining their memorization. The implementation of this method has resulted in the majority of students experiencing an increase in the quality and durability of their memorization, enabling them to complete memorization in a shorter timeframe compared to other methods.